A New Cells‐Compatible Microfluidic Device for Single Channel Recordings. Issue 8 (24th July 2014) - Zanetti, Manuela; Maniglio, Devid; Fasoli, Cristian; Pola, Marco; Borga, Elisa; Corradi, Claudio; Dalla Serra, Mauro; Iannotta, Salvatore; Motta, Antonella; Toccoli, Tullio
Abstract We report the fabrication of a microfluidic apparatus and the realization of a sensors based on PEDOT : PSS, a biocompatible semiconductor polymer used in substitution of standard electrodes for electrophysiological studies and for detection of nanopores in membrane. This gives the possibility to study the mechanisms of ions balance and molecular transport though cell membranes. In particular the apparatus is based on two chambers connected through an aperture in a PTFE sheet where lipid bilayer are formed using Montal‐Mueller method, and the pore‐forming proteins activity is detected by polymeric electrodes. This methodology could be applied to examine different membrane proteins for the purpose of biosensing, drug screening and nanopore technologies.